Selecting the Best of Us? Politician Quality in Village Councils in West Bengal, India - Ananish Chaudhuri; Vegard Iversen; Francesca R. Jensenius; Pushkar Maitra (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Who gets elected to political office? The negative selection hypothesis posits that the inherently dishonest run for office, expecting to earn political rent. Alternatively, the positive selection hypothesis suggests that individuals join politics to make a difference. Developing country politicians are frequently stereotyped as embodiments of the negative selection hypothesis. Using survey and experimental data covering village councils in rural West Bengal, we find that inexperienced village council politicians are less dishonest and more pro-social than ordinary citizens. Our findings also suggest that this idealism wears off with time.
Keywords: C93; O12; O53; Z18; 330; selection into politics; politician quality; corruption; experiments; behavioural games